The impact of internet use on individual earnings in Latin America - Lucas Navarro (Institute for Advanced Development Studies (INESAD), 2010)
This paper uses matching techniques to examine the impact of internet use on individual earnings in six Latin American countries using recent household surveys data. Given their different internet use patterns and their implications, the analysis is done for salaried and self-employed workers separately. While salaried worker users mainly access the internet at work, self employed users access the internet mainly at other places. Therefore, the returns to internet use for salaried workers may be associated not only to individual but also to workplace characteristics. Results indicate a large effect of internet use on earnings for both groups of workers in most of the countries studied. These returns are high compared with estimates for industrialized countries. This could be explained by the much lower prevalence of internet use in the region for the international standards. Additionally, given that the estimations rely on cross-section data, they may not fully control for individuals' characteristics before internet adoption. This calls for the need of panel-data on new ICTs diffusion in the region.
Keywords: L86; O33; O54; 330; Internet use; Internet Impact; Latin America